Morphological and Molecular Comparison of Areolate Grouper (Epinephelus areolatus) from Saudi Arabia and Indonesia (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Grouper (subfamily Epinephelinae) is one of the largest groups of fish in the oceans. Identification of groupers, especially the Epinephelus, is conducted based on morphological characteristics (color, pattern, body shape, and size. However, the identification process is difficult to differentiate morphologically because of their similar characteristics. One method that can be applied is DNA barcoding. This study aimed to compare groupers from Saudi Arabia and Indonesia. Morphological and molecular identification results show that the grouper from this study (from Yanbu, Saudi Arabia, and Lamongan, Indonesia) was Epinephelus areolatus (areolate grouper). Morphologically, grouper samples from Yanbu (Saudi Arabia) were as follows: dorsal fin X-XI/12-15; anal fins II-III/8-9; pectoral fins 13-15; pelvic fin I-5; lateral line scales 48-53; vertebrae 24. Meanwhile, the meristic results of groupers from Lamongan (Indonesia) were as follows: dorsal fins X-XI/15-17; anal fins II-III/8; pectoral fins 16-19; pelvic fin I-5; lateral line scales 48-53; vertebrae 24. The morphological differences between E. areolatus from Saudi Arabia and Indonesia were its spots and caudal fin. Molecular results on E. areolatus showed different clades. Samples from Saudi Arabia belonged to the Western Indian Ocean clade while Indonesia belonged to the Western Pacific. This showed that there were morphological and molecular differences between E. areolatus from Yanbu (Saudi Arabia) and Lamongan (Indonesia). The COI gene sequences of areolate grouper were submitted to NCBI (accession number PP388919.1 for Lamongan and PP388920.1 for Saudi Arabia). This research data can be used as a reference for conservation.